1994
DOI: 10.1007/bf00196393
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium polyphosphate complexes in the mycorrhizal basidiomycete Laccaria bicolor: A 27Al-nuclear magnetic resonance study

Abstract: Abstract. The techniques of 27A1-and 31p-nuclear magnetic resonance (NMR) spectroscopy were used to investigate the interactions of aluminium with intracellular ligands within the mycelium of the ectomycorrhizal basidiomycete Laccaria bicolor (Maire) Orton ($238). The vegetative mycelium was grown on medium containing 0.5 mM A1C13 for 0.5 to 3 d. The 27A1-NMR spectra showed that aluminium was rapidly taken up and accumulated into polyphosphate complexes in the vacuole. Comparison with Al-polyphosphate complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…The A1-F complex was later suggested to be involved in uptake and translocation of A1 (Nagata et al, 1993). A previous study showed that A1 was rapidly taken up and accumulated into polyphosphate complexes in the vacuoles of the mycorrhizal basidiomycete Laccaria bicolor (Martin et al, 1994). In the present study, signals corresponding to neither the A1-F complex nor to the catechins or polyphosphate complexes were observed (Fig.…”
Section: Discussioncontrasting
confidence: 49%
“…The A1-F complex was later suggested to be involved in uptake and translocation of A1 (Nagata et al, 1993). A previous study showed that A1 was rapidly taken up and accumulated into polyphosphate complexes in the vacuoles of the mycorrhizal basidiomycete Laccaria bicolor (Martin et al, 1994). In the present study, signals corresponding to neither the A1-F complex nor to the catechins or polyphosphate complexes were observed (Fig.…”
Section: Discussioncontrasting
confidence: 49%
“…This suggests that polyphosphates in the spore have shorter chain lengths than those in the mycorrhizal state. We note that previous studies showing 31P spectra of ectomycorrhizal roots and free-living ectomycorrhizal (Martin et al, 1985b(Martin et al, , 1994MacFall et al, 1992;Gerlitz and Werk, 1994) contain small or no significant resonances from penultimate or terminal residues. The resonance in Figure 5 representing terminal residues (labeled "b) is larger than that from penultimate residues, which suggests either that there is additional contribution to this resonance either from another compound or from polyphosphates whose penultimate resonances are not visible under highresolution conditions.…”
Section: Cerminating Sporesmentioning
confidence: 51%
“…However, such a complex has not been isolated or identified. In the vacuoles of the mycorrhizal basidiomycete Laccaria bicolor, Al was present in the form of polyphosphate complexes (Martin et al, 1994). Previously, we found that more than two-thirds of the Al in hydrangea leaves was present in the cell sap in a soluble form, and this Al form has been identified as Alcitrate complex at a 1:1 molar ratio of Al to citric acid (Ma et al, 1997a).…”
Section: Discussionmentioning
confidence: 98%